2021
DOI: 10.1186/s12885-021-08882-6
|View full text |Cite
|
Sign up to set email alerts
|

LINC00958 promotes bladder cancer carcinogenesis by targeting miR-490-3p and AURKA

Abstract: Background Bladder cancer is a prevalent malignancy of the urinary system, in which long non-coding RNAs (lncRNAs) are highly associated. We aimed to elucidate the role of LINC00958 in bladder cancer. Methods LINC00958 expression levels were measured using qRT-PCR. The interaction of LINC00958-miR-490-3p-AURKA was analyzed by luciferase, RIP, and RNA pull-down assays. The biological roles of LINC00958, miR-490-3p, and AURKA in bladder cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Our clinical examination results showed upregulated LINC00958 and underexpressed miR-625-5p in BC patients, indicating an inverse connection between the two genes in BC. This is consistent with the results of our previous research and related studies [ 23 , 24 ], confirming that LINC00958 is involved in the occurrence and development of BC and that its mechanism of action may be bound up with miR-625-5p. In the subsequent analysis of the relationship between them and clinical pathology of BC patients, the two genes were found to have a close connection with MI, LNM, DM, and histological grade of BC, which once again verifies our view.…”
Section: Discussionsupporting
confidence: 93%
“…Our clinical examination results showed upregulated LINC00958 and underexpressed miR-625-5p in BC patients, indicating an inverse connection between the two genes in BC. This is consistent with the results of our previous research and related studies [ 23 , 24 ], confirming that LINC00958 is involved in the occurrence and development of BC and that its mechanism of action may be bound up with miR-625-5p. In the subsequent analysis of the relationship between them and clinical pathology of BC patients, the two genes were found to have a close connection with MI, LNM, DM, and histological grade of BC, which once again verifies our view.…”
Section: Discussionsupporting
confidence: 93%
“…Up-regulation of AURKA was correlated with poor outcomes in HCC patients 39 . Functionally, it plays multiple roles in regulating cancer cell proliferation, apoptosis, metastasis, stemness and genomic instability 13,40,41 . In HCC, AURKA promotes cancer metastasis and cancer stem cell properties 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Applying lncRNAs as biomarkers or intervention targets could provide new insights into predicting prognosis, survival and treatment outcome [31,32]. Many studies have shown that lncRNAs play an important role in BCa, and these experimental researches suggested that lncRNAs were associated with the proliferation and invasion of bladder cancer, indicating that they may serve as potential biomarkers for targeted therapy in bladder cancer [20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are emerging regulators involved in gene expression and various physiological and pathological processes. Some scholars believe that abnormal lncRNAs in bladder cancer are closely related to the development and prognosis of the disease, and increasing evidence shows that lncRNAs have the potential to regulate ferroptosis, apoptosis and autophagy in bladder cancer, and play a complex and precise regulatory role in cancer initiation [20][21][22][23][24]. They not only regulate the proliferation, differentiation, invasion and metastasis of cancer cells but also regulate the metabolic reprogramming of cancer cells [25].…”
Section: Introductionmentioning
confidence: 99%